SECTORAL MAPPING OF CREATIVE ECONOMY FIRMS ON THE INDONESIA STOCK EXCHANGE BASED ON KEMENPAREKRAF AND IDX - Soedjatmiko Soedjatmiko; Andi Iswoyo; Nanang Setiawan; Akhmad Julian Saputra (Dinamika Ekonomi: Jurnal Ekonomi dan Bisnis, 2025)
This study aims to map creative economy firms listed on the Indonesia Stock Exchange (IDX) based on the official subsector classification issued by the Ministry of Tourism and Creative Economy (Kemenparekraf) and the IDX Industrial Classification (IDX-IC). Using a descriptive qualitative approach, this study employs content analysis of annual reports, initial public offering (IPO) prospectuses, and other official corporate documents. The classification framework is developed based on indicators of creative activities, intellectual property intensity, and alignment with the 17 nationally defined creative economy subsectors. The findings indicate that only a limited number of IDX-listed firms can be classified as core creative economy companies, with a concentration in the media, film, broadcasting, and advertising subsectors. In contrast, art- and culture-based subsectors such as performing arts, fine arts, crafts, and architecture are largely underrepresented. These findings reveal a structural gap between the strategic role of the creative economy and its capital market representation, while providing a sectoral mapping that supports the development of a creative economy stock index in Indonesia.